Metal slurry for photocuring 3D printing and preparation method and application thereof

By using a combination of metal powder and talc powder with specific ratios in photocuring 3D printing, the settlement of metal materials in liquids and environmental pollution problems are solved, and a metal paste with high stability and environmental protection is achieved, suitable for DLP Photocuring 3D printing.

CN116237516BActive Publication Date: 2024-12-27SHENZHEN ADVENTURE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211632514.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2024-12-27
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

In the existing photocuring 3D printing technology, it is difficult for metal materials to be stablely dispersed in the liquid, resulting in slurry settlement and environmental pollution.

Method used

Using a combination of powder and a carrier, the powder includes metal powder and talc powder, and the carrier includes water, thickener, photocuring resin and stearic acid. Through the design of specific particle sizes and ratios, it forms a high stability and environmentally friendly Metal paste, suitable for DLP photocuring 3D printing.

Benefits of technology

The long-term stability and fluidity of the metal paste are achieved, and the settlement and stratification are avoided. At the same time, water is used as the main solvent to reduce environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116237516B_ABST
    Figure CN116237516B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of 3D printing technology, and specifically discloses a metal slurry for photocuring 3D printing and its preparation method and application. Wherein, the metal slurry includes a powder and a carrier, and the weight ratio of the carrier and the powder is (1-1.5): (5-10); the powder includes the following components in parts by weight: 90-100 parts of metal powder, 4-10 parts of talcum powder; the carrier includes, by weight: 30-60 parts of water, 0.5-8 parts of thickener, 40-70 parts of photocurable resin, 8-25 parts of stearic acid, 0.5-5 parts of photoinitiator; the average particle size of the metal powder is 5-150 μm, fluidity is ≤35 mm, and the average particle size of the talcum powder is 0.5-3 μm. Implementation of the present invention can obtain a metal slurry with strong stability and more environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of 3D printing, and in particular to a metal slurry for photocuring 3D printing and a preparation method and application thereof. Background Art

[0002] Additive manufacturing or 3D printing is a "bottom-up" material accumulation manufacturing method. Currently, the most commonly used methods in the field of metal additive manufacturing include powder bed fusion technology, material jetting process, binder jetting method and direct energy deposition. Although photocuring 3D printing technology is widely used in other materials such as polymers, ceramics, hydrogels, etc., there are relatively few studies on photocuring metal 3D printing. Since metal materials generally have a high density, they usually settle immediately in the liquid and it is difficult to stably disperse them in the photocuring liquid to form a slurry. Photocuring 3D printing must be achieved with the help of photocuring slurry, so it is necessary to develop photocuring metal 3D slurry with high stability.

[0003] On the other hand, most of the photocurable slurries currently used use high molecular weight organic solvents (such as paraffin, polylactic acid, etc.) as diluents. During the printing and cleaning processes, the use of organic solvents will cause environmental pollution. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a metal slurry for photocuring 3D printing and a preparation method thereof, which has strong stability and is more environmentally friendly.

[0005] In order to solve the above problems, the present invention discloses a metal slurry for photocuring 3D printing, which comprises a powder and a carrier, wherein the weight ratio of the carrier to the powder is (1-1.5): (5-10);

[0006] Wherein, the powder comprises the following components in parts by weight:

[0007] 90-100 parts of metal powder, 4-10 parts of talc;

[0008] The carrier comprises, by weight:

[0009] 30-60 parts of water, 0.5-8 parts of thickener, 40-70 parts of photocurable resin, 8-25 parts of stearic acid, 0.5-5 parts of photoinitiator;

[0010] The average particle size of the metal powder is 5-150 μm, the fluidity is ≤35 mm, and the average particle size of the talc powder is 0.5-3 μm.

[0011] As an improvement of the above technical solution, the average particle size of the talcum powder is 1-2 μm.

[0012] As an improvement of the above technical solution, the particle size of the metal powder meets the following relationship: (D90-D10) / D50=2-3.

[0013] As an improvement of the above technical solution, the metal powder is selected from one or more of copper powder, aluminum powder, gold powder and silver powder.

[0014] As an improvement of the above technical solution, the thickener is selected from one or more of sodium alginate, pectin, polyvinyl alcohol, methyl cellulose, and sodium carboxymethyl cellulose.

[0015] As an improvement of the above technical solution, the photocurable resin is selected from one or more of water-based polyacrylate, water-based polyester acrylate, water-based epoxy acrylate, and water-based polyurethane acrylate.

[0016] As an improvement of the above technical solution, the thickener is sodium carboxymethyl cellulose, and the photocurable resin is water-based polyacrylate.

[0017] As an improvement of the above technical solution, the O content in the metal powder is ≤100ppm.

[0018] Correspondingly, the present invention also discloses a method for preparing a metal slurry for photocuring 3D printing, which is used to prepare the above-mentioned metal slurry for photocuring 3D printing, and comprises:

[0019] The thickener, stearic acid and water are mixed, and then mixed with a light-curable resin, stearic acid and a photoinitiator to obtain a carrier;

[0020] Metal powder, talcum powder and a carrier are mixed to obtain a metal slurry for photocuring 3D printing.

[0021] Correspondingly, the present invention also discloses the application of the above-mentioned metal slurry for photocuring 3D printing in DLP photocuring 3D printing.

[0022] The implementation of the present invention has the following beneficial effects:

[0023] The metal slurry for photocuring 3D printing of the present invention comprises a powder and a carrier, wherein the powder comprises 15-100 parts of metal powder and 5-10 parts of talcum powder; the carrier comprises 80-100 parts of water, 1-10 parts of thickener, 10-20 parts of photocuring resin, and 1-5 parts of stearic acid. The metal slurry obtained based on the above powder and carrier has strong stability and does not settle after being placed for a long time; and has reasonable fluidity, which is convenient for forming by DLP photocuring 3D printing process. In addition, the metal slurry uses water as the main solvent and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1is an electron microscope image of the copper powder used in one embodiment of the present invention;

[0025] Figure 2 1 is a graph showing the sedimentation test results of the metal slurries obtained in Example 1 and Comparative Example 1 of the present invention;

[0026] Figure 3 1 is a graph showing the results of the sedimentation experiments of the metal slurries obtained in Example 1 and Comparative Example 2 of the present invention;

[0027] Figure 4 1 is a graph showing the sedimentation test results of the metal slurries obtained in Example 1 and Comparative Example 3 of the present invention;

[0028] Figure 5 1 is a graph showing the results of a sedimentation experiment of the metal slurries obtained in Example 1 and Example 2 of the present invention;

[0029] Figure 6 This is a metal blank image obtained by printing the metal slurry obtained in Example 1 and Example 2 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in further detail below.

[0031] The present invention provides a metal slurry for photocuring 3D printing, which comprises a powder and a carrier, wherein the weight ratio of the carrier to the powder is (1-1.5):(5-10); the metal slurry of the present invention has a high solid phase content, and the printed components have high dimensional accuracy and high strength.

[0032] Wherein, the powder includes the following components in parts by weight:

[0033] 90-100 parts of metal powder, 4-10 parts of talc;

[0034] The average particle size of the talc is 0.5-3 μm, exemplarily 0.7 μm, 0.9 μm, 1.2 μm, 2 μm or 2.5 μm, but not limited thereto. The inventor unexpectedly discovered that when a specific ratio of talc with the above particle size is introduced, the stability of the metal slurry can be effectively improved, so that it does not settle or stratify when placed for 1 month.

[0035] Preferably, the particle size of talcum powder is 1-2 μm. After using talcum powder of this particle size, metal powder with a larger particle size can be used, such as metal powder with an average particle size of 50-150 μm. Metal powder with a larger particle size is beneficial to improving the strength of printed components.

[0036] Specifically, the metal powder may be a single metal powder, such as copper powder, aluminum powder, gold powder, silver powder, but not limited thereto. The metal powder may also be a mixture of two or more metal powders. The metal powder may also be an alloy powder.

[0037] Specifically, the average particle size of the metal powder is 5-150 μm (measured by a laser particle size analyzer, D50), and the fluidity is ≤35 mm. Based on the above properties, the metal powder can form a metal slurry with a high solid phase ratio and reasonable viscosity, providing a good foundation for DLP light-curing printing.

[0038] Among them, the test method for liquidity is:

[0039] Place a smooth metal cylinder with a diameter of 30 mm and a height of 50 mm on a glass plate, fill it with metal powder and scrape it flat, then lift the glass cylinder. After the metal plate powder naturally disperses, record the maximum height H of the pile. s , then liquidity is calculated as follows:

[0040] f=50-H s

[0041] Where f is the fluidity of the metal powder, H s It is the maximum height of the pile formed during the flowability test.

[0042] Preferably, in one embodiment of the present invention, the particle size of the metal powder meets the following relationship: (D90-D10) / D50=2-3, wherein D10 is the particle size at 10% of the cumulative distribution of particles, D50 is the particle size at 50% of the cumulative distribution of particles (i.e., the average particle size), and D90 is the particle size at 90% of the cumulative distribution of particles, and D10, D50, and D90 are all measured by a laser particle size analyzer. Based on the above control of the particle size of the metal powder, the stability of the metal slurry can be greatly improved, so that it still does not stratify or settle after being placed for 3 months.

[0043] Preferably, in one embodiment of the present invention,

[0044] The O content in the metal powder is ≤100 ppm, preferably 10-80 ppm, and the overflow of O in the subsequent sintering process will cause a decrease in dimensional accuracy.

[0045] The carrier is mainly used to carry and disperse the powder. Specifically, it includes the following components in parts by weight:

[0046] 30-60 parts of water, 0.5-8 parts of thickener, 40-70 parts of photocurable resin, 8-25 parts of stearic acid, and 0.5-5 parts of photoinitiator; the carrier based on the above components makes the metal slurry free of agglomeration and caking, has reasonable fluidity, and does not settle for a long time.

[0047] The thickener is selected from one or more of sodium alginate, pectin, polyvinyl alcohol, methyl cellulose, and sodium carboxymethyl cellulose, preferably sodium carboxymethyl cellulose.

[0048] The photocurable resin is selected from one or more of waterborne polyacrylate, waterborne polyester acrylate, waterborne epoxy acrylate, and waterborne polyurethane acrylate, but is not limited thereto. Preferably, waterborne polyacrylate is selected.

[0049] Among them, stearic acid can promote the uniform distribution of metal powder and reduce the flow viscosity of metal slurry.

[0050] The photoinitiator can be selected according to the specific photocurable resin. For example, when water-based epoxy acrylate is selected as the photocurable resin, TPO can be used as the photocuring agent.

[0051] Correspondingly, the present invention also discloses a method for preparing a metal slurry for photocuring 3D printing, which is used to prepare the above-mentioned metal slurry for photocuring 3D printing, and comprises:

[0052] (1) mixing a thickener, stearic acid and water, and then mixing with a photocurable resin, stearic acid and a photoinitiator to obtain a carrier;

[0053] (2) Metal powder, talcum powder and a carrier are mixed to obtain a metal slurry for photocuring 3D printing.

[0054] The mixing can be performed using a common mixing device in the art. Preferably, in one embodiment of the present invention, a ball mill is used for mixing, the speed of the ball mill is 10-1000 rpm, and the ball milling mixing time is 5-500 min.

[0055] The present invention will be further described below with specific implementation:

[0056] Example 1

[0057] This embodiment provides a metal slurry for photocuring 3D printing, including a powder and a carrier, wherein the weight ratio of the carrier to the powder is 1.1:6;

[0058] Among them, the powder formula is:

[0059] 95 parts of copper powder, 5 parts of talcum powder;

[0060] The average particle size of the copper powder is 40 μm, the fluidity is 32 mm, (D90-D10) / D50=5.5, the O content is 80 ppm, and the average particle size of the talc powder is 2.5 μm.

[0061] The carrier formula is:

[0062] 50 parts of water, 0.5 parts of sodium carboxymethyl cellulose, 50 parts of water-based polyester acrylate, 10 parts of stearic acid, and 1 part of photoinitiator 1173.

[0063] The preparation method of the metal slurry is:

[0064] Sodium carboxymethyl cellulose was dissolved in water, and then aqueous polyester acrylate, stearic acid and photoinitiator 1173 were added, copper powder and talc were added after mixing, and the mixture was mixed in a ball mill for 1 hour to obtain a slurry.

[0065] Example 2

[0066] This embodiment provides a metal slurry for photocuring 3D printing, including a powder and a carrier, wherein the weight ratio of the carrier to the powder is 1.1:6;

[0067] Among them, the powder formula is:

[0068] 95 parts of copper powder, 5 parts of talcum powder;

[0069] The average particle size of the copper powder is 120 μm, the fluidity is 20 mm, (D90-D10) / D50=2.5, the O content is 80 ppm, and the average particle size of the talc powder is 1.5 μm.

[0070] The carrier formula is:

[0071] 50 parts of water, 0.5 parts of sodium carboxymethyl cellulose, 50 parts of water-based polyester acrylate, 10 parts of stearic acid, and 1 part of photoinitiator 1173.

[0072] The preparation method of the metal slurry is:

[0073] Sodium carboxymethyl cellulose was dissolved in water, and then aqueous polyester acrylate, stearic acid and photoinitiator 1173 were added, copper powder and talc were added after mixing, and the mixture was mixed in a ball mill for 1 hour to obtain a slurry.

[0074] Example 3

[0075] This embodiment provides a metal slurry for photocuring 3D printing, including a powder and a carrier, wherein the weight ratio of the carrier to the powder is 1.2:8;

[0076] Among them, the powder formula is:

[0077] 95 parts of copper powder, 5 parts of talcum powder;

[0078] The average particle size of the copper powder is 120 μm, the fluidity is 20 mm, (D90-D10) / D50=2.5, the O content is 80 ppm, and the average particle size of the talc powder is 1.5 μm.

[0079] The carrier formula is:

[0080] 50 parts of water, 0.5 parts of sodium carboxymethyl cellulose, 50 parts of water-based polyester acrylate, 10 parts of stearic acid, and 1 part of photoinitiator 1173.

[0081] The preparation method of the metal slurry is:

[0082] Sodium carboxymethyl cellulose was dissolved in water, and then aqueous polyester acrylate, stearic acid and photoinitiator 1173 were added, copper powder and talc were added after mixing, and the mixture was mixed in a ball mill for 1 hour to obtain a slurry.

[0083] Example 4

[0084] This embodiment provides a metal slurry for photocuring 3D printing, including a powder and a carrier, wherein the weight ratio of the carrier to the powder is 1.3:8;

[0085] Among them, the powder formula is:

[0086] 98 parts of copper powder, 2 parts of talcum powder;

[0087] The average particle size of the copper powder is 150 μm, the fluidity is 15 mm, (D90-D10) / D50=2.3, the O content is 80 ppm, and the average particle size of the talc powder is 1.5 μm.

[0088] The carrier formula is:

[0089] 30 parts of water, 4 parts of polyvinyl alcohol, 65 parts of water-based epoxy acrylate, 25 parts of stearic acid, and 3 parts of photoinitiator TPO.

[0090] The preparation method of the metal slurry is:

[0091] Polyvinyl alcohol was dissolved in water, and then waterborne epoxy acrylate, stearic acid and photoinitiator TPO were added, copper powder and talc were added after mixing, and the mixture was mixed in a ball mill for 1 hour to obtain a slurry.

[0092] Example 5

[0093] This embodiment provides a metal slurry for photocuring 3D printing, including a powder and a carrier, wherein the weight ratio of the carrier to the powder is 1.3:8;

[0094] Among them, the powder formula is:

[0095] 98 parts of copper powder, 2 parts of talcum powder;

[0096] The average particle size of the copper powder is 120 μm, the fluidity is 10 mm, (D90-D10) / D50=1.3, the O content is 80 ppm, and the average particle size of the talc powder is 1.5 μm.

[0097] The carrier formula is:

[0098] 30 parts of water, 4 parts of polyvinyl alcohol, 65 parts of water-based epoxy acrylate, 25 parts of stearic acid, and 3 parts of photoinitiator TPO.

[0099] The preparation method of the metal slurry is:

[0100] Polyvinyl alcohol was dissolved in water, and then waterborne epoxy acrylate, stearic acid and photoinitiator TPO were added, copper powder and talc were added after mixing, and the mixture was mixed in a ball mill for 1 hour to obtain a slurry.

[0101] Comparative Example 1

[0102] This comparative example provides a metal slurry for photocuring 3D printing, including a powder and a carrier, wherein the weight ratio of the carrier to the powder is 1.1:6;

[0103] Among them, the powder formula is:

[0104] 95 parts of copper powder, 5 parts of talcum powder;

[0105] The average particle size of the copper powder is 180 μm, the fluidity is 10 mm, (D90-D10) / D50=5.5, and the O content is 80 ppm. The average particle size of the talc powder is 2.5 μm.

[0106] The carrier formula is:

[0107] 50 parts of water, 0.5 parts of sodium carboxymethyl cellulose, 50 parts of water-based polyester acrylate, 10 parts of stearic acid, and 1 part of photoinitiator 1173.

[0108] The preparation method of the metal slurry is:

[0109] Sodium carboxymethyl cellulose was dissolved in water, and then aqueous polyester acrylate, stearic acid and photoinitiator 1173 were added, copper powder and talc were added after mixing, and the mixture was mixed in a ball mill for 1 hour to obtain a slurry.

[0110] The metal slurry obtained in Example 1 and Comparative Example 1 was placed in a test tube and observed after standing for 1 hour ( Figure 2 ), it can be seen that the metal slurry of comparative example 2 has obvious sedimentation and stratification (left). However, the metal slurry of example 1 has no obvious sedimentation (right).

[0111] Comparative Example 2

[0112] This comparative example provides a metal slurry for photocuring 3D printing, including a powder and a carrier, wherein the weight ratio of the carrier to the powder is 1.1:6;

[0113] Among them, the powder formula is:

[0114] 95 parts of copper powder, 5 parts of talcum powder;

[0115] The average particle size of the copper powder is 2 μm, the fluidity is 45 mm, (D90-D10) / D50=3.5, and the O content is 80 ppm. The average particle size of the talc powder is 2.5 μm.

[0116] The carrier formula is:

[0117] 50 parts of water, 0.5 parts of sodium carboxymethyl cellulose, 50 parts of water-based polyester acrylate, 10 parts of stearic acid, and 1 part of photoinitiator 1173.

[0118] The preparation method of the metal slurry is:

[0119] Sodium carboxymethyl cellulose was dissolved in water, and then aqueous polyester acrylate, stearic acid and photoinitiator 1173 were added, copper powder and talc were added after mixing, and the mixture was mixed in a ball mill for 1 hour to obtain a slurry.

[0120] The metal slurry obtained in Example 1 and Comparative Example 2 was placed in a test tube and left to stand for 1 hour before observation ( Figure 3 ), it can be seen that the metal slurry of comparative example 2 has obvious sedimentation and stratification (left). However, the metal slurry of example 1 has no obvious sedimentation (right).

[0121] Comparative Example 3

[0122] This comparative example provides a metal slurry for photocuring 3D printing, including a powder and a carrier, wherein the weight ratio of the carrier to the powder is 1.1:6;

[0123] Among them, the powder formula is:

[0124] 100 parts of copper powder;

[0125] The average particle size of the copper powder is 2 μm, the fluidity is 45 mm, (D90-D10) / D50=3.5, and the O content is 80 ppm. The average particle size of the talc powder is 2.5 μm.

[0126] The carrier formula is:

[0127] 50 parts of water, 0.5 parts of sodium carboxymethyl cellulose, 50 parts of water-based polyester acrylate, 10 parts of stearic acid, and 1 part of photoinitiator 1173.

[0128] The preparation method of the metal slurry is:

[0129] Sodium carboxymethyl cellulose was dissolved in water, and then aqueous polyester acrylate, stearic acid and photoinitiator 1173 were added, copper powder and talc were added after mixing, and the mixture was mixed in a ball mill for 1 hour to obtain a slurry.

[0130] The metal slurry obtained in Example 1 and Comparative Example 3 was placed in a test tube and observed after standing for 1 hour ( Figure 4), it can be seen that the metal slurry of comparative example 3 has obvious sedimentation and stratification (left). However, the metal slurry of example 1 has no obvious sedimentation (right).

[0131] Take the metal slurry obtained in Example 1 and Example 2, put it in a test tube, and observe the situation after standing for 3 months ( Figure 5 ), it can be seen from the figure that the metal slurry of Example 1 has a small amount of sedimentation and stratification (left), while the slurry obtained in Example 2 has no stratification. It can be seen that controlling the copper powder (D90-D10) / D50=2.5 ​​can effectively improve the stability of the metal slurry.

[0132] After the sedimentation experiment was conducted for 3 months, the metal slurries of Example 1 and Example 2 were shaken and then printed using an ADT-ZP-DLP series 3D printer produced by Shenzhen Qiyu Technology Co., Ltd. The printed samples were as shown in FIG. Figure 6 As shown, it can be seen that the metal slurries of Example 1 (left) and Example 2 (right) can both print high-precision green bodies.

[0133] The above is a preferred embodiment of the invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the invention. These improvements and modifications are also considered to be within the scope of protection of the invention.

Claims

1. A metal slurry for photocuring 3D printing, characterized in that: It comprises a powder and a carrier, wherein the weight ratio of the carrier to the powder is (1-1.5): (5-10); Wherein, the powder comprises the following components in parts by weight: 90-100 parts of metal powder, 4-10 parts of talc; The carrier comprises, by weight: 30-60 parts of water, 0.5-8 parts of thickener, 40-70 parts of photocurable resin, 8-25 parts of stearic acid, 0.5-5 parts of photoinitiator; The metal powder has an average particle size of 5-150 μm and a fluidity of ≤35 mm; the talcum powder has an average particle size of 0.5-3 μm; the thickener is polyvinyl alcohol; and the photocurable resin is water-based polyacrylate.

2. The metal slurry for photocuring 3D printing according to claim 1, characterized in that: The average particle size of the talc is 1-2 μm.

3. The metal slurry for photocuring 3D printing according to claim 1, characterized in that: The particle size of the metal powder meets the following relationship: (D90-D10) / D50=2-3.

4. The metal slurry for photocuring 3D printing according to any one of claims 1 to 3, characterized in that: The metal powder is selected from one or more of copper powder, aluminum powder, gold powder and silver powder.

5. The metal slurry for photocuring 3D printing according to claim 1, characterized in that: The O content in the metal powder is ≤100ppm.

6. A method for preparing a metal slurry for photocuring 3D printing, for preparing the metal slurry for photocuring 3D printing as claimed in any one of claims 1 to 5, characterized in that: include: The thickener, stearic acid and water are mixed, and then mixed with a light-curable resin, stearic acid and a photoinitiator to obtain a carrier; Metal powder, talcum powder and a carrier are mixed to obtain a metal slurry for photocuring 3D printing.

7. Application of the metal slurry for photocuring 3D printing as described in any one of claims 1 to 5 in DLP photocuring 3D printing.